Un parcours de collectionneur privé « chalinologue » - Pierre-Marie Desclos (In Situ)
A ‘chalinologue’, a private collector of horses’ bits. Monsieur Desclos is a passionate collector of old bits, particularly interested in the technology of bits and by ‘system’ bits. He has accumulated a considerable collection, along with associated and digitized documentary files, largely based on old treatises. His collection therefore has a detailed inventory of the items it is comprised of. Like many private collectors, his acquisitions are restrained by a limited budget and also by the lack of space to display the thousand odd pieces in the collection. Cataloguing, upkeep and restoration are constant preoccupations, along with the desire to transmit and to share this collection and the know-how that accompanies it.